Genetic Manipulation of DNA and Protein Examples from Current Research - Figurski, David (IntechOpen, 2013)
This diverse collection of research articles is united by the enormous power of modern molecular genetics. Every author accomplished two objectives: (1) making the field and the research described accessible to a large audience and (2) explaining fully the genetic tools and approaches that were used in the research. One fact stands out - the importance of a genetic approach to addressing a problem. I encourage you to read several chapters. You will feel the excitement of the scientists, and you will learn about an area of research with which you may not be familiar. Perhaps most importantly, you will understand the genetic approaches; and you will appreciate their importance to the research.